A comparison of the degree of implementation of marine biodiversity indicators by European countries in relation to the Marine Strategy Framework Directive (MSFD). (23rd June 2015) - Hummel, Herman; Frost, Matt; Juanes, José A.; Kochmann, Judith; Castellanos Perez Bolde, Carlos F.; Aneiros, Fernando; Vandenbosch, François; Franco, João N.; Echavarri, Beatriz; Guinda, Xabier; Puente, Araceli; Fernández, Camino; et al.
Abstract : The degree of development and operability of the indicators for the Marine Strategy Framework Directive (MSFD) using Descriptor 1 (D1) Biological Diversity was assessed. To this end, an overview of the relevance and degree of operability of the underlying parameters across 20 European countries was compiled by analysing national directives, legislation, regulations, and publicly available reports. Marked differences were found between countries in the degree of ecological relevance as well as in the degree of implementation and operability of the parameters chosen to indicate biological diversity. The best scoring EU countries were France, Germany, Greece and Spain, while the worst scoring countries were Italy and Slovenia. No country achieved maximum scores for the implementation of MSFD D1. The non-EU countries Norway and Turkey score as highly as the top-scoring EU countries. On the positive side, the chosen parameters for D1 indicators were generally identified as being an ecologically relevant reflection of Biological Diversity. On the negative side however, less than half of the chosen parameters are currently operational. It appears that at a pan-European level, no consistent and harmonized approach currently exists for the description and assessment of marine biological diversity. The implementation of the MSFD Descriptor 1 for Europe as a whole can therefore at best be marked as moderately successful.